Taking empowerment into account: the response of community-based organisations to the HIV care needs of men who have sex with men in West Africa (CohMSM ANRS 12324 – Expertise France). Issue 11 (2nd November 2019) - Coulaud, Pierre-Julien; Préau, Marie; Maradan, Gwenaelle; Mora, Marion; Traoré, Fodé; Oga, Maxime; Thio, Elisabeth; Ekon, Lorette; Dembele Keita, Bintou; Anoma, Camille; Ter Tiero Dah, Elias; Mensah, Ephrem; et al.
ABSTRACT: Empowerment is an ongoing process through which individuals and communities appropriate power and acquire the capability to function autonomously. Research on empowerment in men who have sex with men (MSM) is lacking in community-based contexts. We investigated the relationship between willingness to be empowered and HIV care needs in West African MSM accessing community-based organisations' (CBO) services. Fifty-three interviews were administered to HIV-negative MSM participating in the CohMSM study (Mali, Burkina Faso, Côte d'Ivoire, Togo). Five indicators of empowerment were identified from a discourse analysis: (i) motivation to access HIV services, (ii) willingness to improve HIV services, (iii) desire to be involved in new activities, (iv) desire to participate in such services, (v) willingness to collaborate in decision making. Based on these indicators, participants were classified into two profiles: high (19/53, 36%) and low (34/53, 64%) level of willingness to be empowered (HWE, LWE). Using a thematic analysis, HWE participants were focused on collective benefit (preventive follow-up, questions about MSM identity), while LWE participants were centred on individual benefit (medical care). CBOs should consider empowerment as a tool to advance collective health benefits for MSM. To improve empowerment in MSM, specific training on issues regarding sexual identity and stigma is needed for CBO providers.